Model Pemberdayaan Ekonomi Masyarakat Nelayan (Studi Sistem Bagi Hasil Perikanan di Wilayah Madura) - Saidi, Muhammad (Program Doktor Ilmu Ekonomi, 2014)
This research aims to develop the model of economic empowerment of fishing communities with a focus of study for fishery system practiced fishing communities, the fisherman owner (skipper) with fishermen cultivators (labor). Research conducted in a number of locations in the coastal region of Madura which includes Bangkalan, Sampang, Pamekasan and Sumenep with a wide range of revenue-sharing system. Qualitative research method using a phenomenological approach. Data was collected through in-depth interviews and direct observation in the field. The data were analyzed qualitatively phenomenological, with the implied meaning uncovering what is seen, felt, experienced and/or do the informants and investigators, and also calculates the quantitative results between fishermen and fishermen owner cultivators, fishery production value do with fishing income per year and per month in household wellbeing of fishermen. Results of this research get that: (1) the distribution of revenues fishery is conducted with a profit-sharing between fishermen owners with tenant fishermen, but the results are applied to the Madurese community almost everything is not in accordance with the provisions of the law No.16/1964, just in Coastal Ambunten, Sumenep with a variation of the results in accordance with its provisions; (2) almost all fishermen tenants in Madura according to World Bank criteria and classified should not prosperous or poor, and (3) model of emprovement that can improve the economic of fisher families are models that do by financiers/marketers (pangamba’). Financiers/marketer (pangamba’) gives some compen-sation to fishermen who became his partner and the compensation results into venture capital. Keywords: Profit Sharing System, Economic Empowerment, Fishermen